2015
DOI: 10.1104/pp.15.01171
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A and B Function Antagonistically to Regulate Cold Tolerance via Abscisic Acid-Dependent Jasmonate Signaling

Abstract: Light signaling and phytohormones both influence plant growth, development, and stress responses; however, cross talk between these two signaling pathways in response to cold remains underexplored. Here, we report that far-red light (FR) and red light (R) perceived by phytochrome A (phyA) and phyB positively and negatively regulated cold tolerance, respectively, in tomato (Solanum lycopersicum), which were associated with the regulation of levels of phytohormones such as abscisic acid (ABA) and jasmonic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
198
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(219 citation statements)
references
References 70 publications
(80 reference statements)
8
198
1
1
Order By: Relevance
“…The residue was resuspended in 0.5 mL of 70% (v/v) methanol and centrifuged at 18,000g for 2 min at 4°C. The final supernatants were pipetted into glass vials and then analyzed by HPLC-MS/MS (Agilent 6460; Agilent Technologies) using the same method described previously (Wang et al, 2016).…”
Section: Measurement Of Phytohormone Contentmentioning
confidence: 99%
“…The residue was resuspended in 0.5 mL of 70% (v/v) methanol and centrifuged at 18,000g for 2 min at 4°C. The final supernatants were pipetted into glass vials and then analyzed by HPLC-MS/MS (Agilent 6460; Agilent Technologies) using the same method described previously (Wang et al, 2016).…”
Section: Measurement Of Phytohormone Contentmentioning
confidence: 99%
“…In addition to their roles in plant photomorphogenesis, cross-talk between phytochrome-mediated light signals and cold signaling pathways has been identified in the model plant Arabidopsis and tomato (Williams et al, 1972; Kim et al, 2002; Wang et al, 2016). As early as 1972, Williams et al noticed that phytochrome could mediate short day enhancement of cold acclimation, but the molecular basis for phytochrome regulation of cold tolerance remained unknown until recent years (Williams et al, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the freezing tolerance of short-day plants was increased relative to that of LD plants in Arabidopsis (Lee and Thomashow, 2012). Wang et al (2016) found that FR and R light perceived by phyA and phyB positively and negatively regulated cold tolerance, respectively, in tomato ( Solanum lycopersicum ). FR light-induced activation of phyA triggers ABA signaling and, subsequently, JA signaling, leading to activation of the CBF pathway and a cold response in tomato plants (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptors modify plant growth, development, and stress responses via alterations in phytohormone homeostasis (Jiao et al, 2007;Wang et al, 2016). Like polar auxin transport (PAT), light-induced signaling is basipetal in direction.…”
Section: Phyb-mediated Auxin Signaling Is Required For the Systemic Ementioning
confidence: 99%